Health‐related quality of life and long‐term related conditions in survivors of epidermal necrolysis: a study of 57 patients. (31st March 2020) - Ingen‐Housz‐Oro, S.; Alves, A.; Colin, A.; Ouedraogo, R.; Layese, R.; Canoui‐Poitrine, F.; Chosidow, O.; Mekontso‐Dessap, A.; Wolkenstein, P.; de Prost, N.
Abstract : Summary: Epidermal necrolysis (EN), including Stevens‐Johnson syndrome and toxic epidermal necrolysis (or Lyell syndrome), are life‐threatening drug reactions which cause blistering and sloughing of skin and mucous membranes. They represent a single disease with a spectrum of severity. Mortality (death) rate at the acute, meaning more severe, phase varies from 15 to 30%. Supportive care is the cornerstone of treatment. Some patients need care in an intensive care unit (ICU) or burn unit. The aim of the current study was to investigate the long‐term health‐related quality of life (HR‐QoL) of EN survivors, and other conditions they later experienced as a result of EN (known as sequelae). We conducted a study of patients admitted to a hospital for EN between 2010 and 2017. HR‐QoL was assessed during a phone interview by using different ways of measuring a person's quality of life: the SF‐36 questionnaire, Hospital Anxiety and Depression (HAD) scale, Impact of Event Scale‐Revised (IES‐R), and general QoL outcomes, including specific sequelae. The primary (main) outcome measure was the physical component summary (PCS) score of the SF‐36. In this, higher scores show higher (or better) quality of life, while lower scores show a worse quality of life. In total, 57 EN survivors, including 19 who had been admitted in the ICU, were phone‐interviewed at a median of 3.6 years after hospital discharge. The median SF36 physical component score (PCS) was below that of the age‐sex‐matched reference population (meaning people of the same age and sex but who had not had EN), and was significantly lower for EN survivors admitted versus not admitted to the ICU. The proportion of patients with high anxiety and depression scores was 54% and 21%, respectively. Reported specific sequelae were cutaneous, meaning they affected the skin (77%), ocular (eyes, 70%), psychological (60%), dental/oral (49%), genital (30%) and respiratory (breathing/ lungs, 18%). Our study confirms the major burden and long‐term impact of EN on quality of life of survivors and emphasizes the need for prolonged close follow‐up after the acute phase of EN. This is a summary of the study: Health‐related quality of life and long‐term sequelae in survivors of epidermal necrolysis: an observational study of 57 patients